2019
DOI: 10.1200/jco.2019.37.7_suppl.545
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study investigating the safety and efficacy of savolitinib and durvalumab in metastatic papillary renal cancer (CALYPSO).

Abstract: 545 Background: Metastatic papillary renal cancer (PRC) has poor outcomes and there is need for new treatments. There is a strong rationale for investigating MET and PD-L1 inhibition in this disease. In this study, we investigate savolitinib (MET inhibitor) and durvalumab (PD-L1 inhibitor) together. Methods: This single arm phase I/II trial explored durvalumab and savolitinib at starting doses of 1500mg Q4W and 600mg OD respectively, with a 4wk savolitinib run-in. Treatment naïve or previously treated patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 0 publications
0
34
0
1
Order By: Relevance
“…Data from prospective studies are also available. In the CALYPSO phase I/II trial utilizing the combination of savolitinib and durvalumab a response rate of 27% was achieved in patients with papillary renal cell carcinoma (pRCC) [73]. Finally, in the cohort B of the KEYNOTE 427B trial, 165 patients with recurrent, or metastatic papillary (71%), chromophobe (13%), or unclassified (16%).…”
Section: Non-clear-cell Renal Carcinomamentioning
confidence: 99%
“…Data from prospective studies are also available. In the CALYPSO phase I/II trial utilizing the combination of savolitinib and durvalumab a response rate of 27% was achieved in patients with papillary renal cell carcinoma (pRCC) [73]. Finally, in the cohort B of the KEYNOTE 427B trial, 165 patients with recurrent, or metastatic papillary (71%), chromophobe (13%), or unclassified (16%).…”
Section: Non-clear-cell Renal Carcinomamentioning
confidence: 99%
“…For patients with intermediate-risk or poor-risk disease according to the IMDC score (Escudier et al 2007), independent of PD-L1 status, the panelists suggest treatment with a combination of nivolumab plus ipilimumab (an anti-PD-1 plus anti-CTLA-4 agents) or pembrolizumab plus axitinib, according to local access to therapies (recommendation level A) (Motzer et al 2018a, b;Powles et al 2019a, b). The CheckMate 214 study found that compared to sunitinib (50 mg) orally once daily for 4 weeks (over a 6-week cycle), immunotherapy combined with anti-PD1/CTLA4 agents resulted in significant improvements in the primary objectives of OS and objective response rate (ORR) and numerically progression-free survival in intermediate/poor-risk patients score in a primary analysis of 25.2 months and a follow-up analysis of 32.4 months (Motzer et al 2018a(Motzer et al , b, 2019a.…”
Section: First-line Treatment For Advanced Rcc: What To Choose?mentioning
confidence: 99%
“…Still based on scientific evidence from the KEY-NOTE-426 study, the panelists recommend that patients with the good-risk disease, independent of PD-L1 status, should also be treated with the combination of immunotherapy plus TKI (pembrolizumab plus axitinib) (recommendation level A) (Powles et al 2019a, b).…”
Section: First-line Treatment For Advanced Rcc: What To Choose?mentioning
confidence: 99%
“…The ORR was more pronounced in those with tumors that had a PD-L1 combined positive score (CPS) of ≥ 1% (35.3%) compared to a CPS < 1% (10.3%). A second single-arm phase I/II trial enrolled both treatmentnaïve and previously treated patients with papillary mRCC to receive combination therapy with savolitinib (a MET-targeting TKI) and durvalumab [24]. In the 28 treatment-naïve patients, the ORR was 29% and median PFS was 12 months (95% CI 1.5-NR).…”
Section: Cpi-based Regimens In Non-clear Cell Metastatic Renal Cell Cmentioning
confidence: 99%